2017
DOI: 10.3390/ijms18071501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein-Iron Complex Concentrate Supplementation on Iron Metabolism, Oxidative and Immune Status in Preweaning Calves

Abstract: The objective of this study was to determine the effects of feeding protein-iron complex (PIC) on productive performance and indicators of iron metabolism, hematology parameters, antioxidant and immune status during first 35 days of a calf’s life. Preparation of the complex involved enzymatic hydrolysis of milk casein (serine protease from Yarrowia lipolytica yeast). Iron chloride was then added to the hydrolyzate and lyophilizate. Calves were divided into treated groups: LFe (low iron dose) 10 g/day calf of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
6
15
1
Order By: Relevance
“…According to Tanaka et al (2014), IL-6 might have multiple functions, stimulating inflammatory conditions and inhibiting TNF-α production (Tokarz-Deptuła et al, 2011). The influence of food on TNF-α levels is, to some extent, confirmed by other studies (Hulbert et al, 2011;Kupczyński et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to Tanaka et al (2014), IL-6 might have multiple functions, stimulating inflammatory conditions and inhibiting TNF-α production (Tokarz-Deptuła et al, 2011). The influence of food on TNF-α levels is, to some extent, confirmed by other studies (Hulbert et al, 2011;Kupczyński et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
“…The first weeks of a calf's life particularly have a key effect on its future performance and on production cost-effectiveness (Bateman et al, 2012;Garcia et al, 2016). Calf milk replacers (MR) tend to include various additives, such as protein-iron complex, butyrates, canola, linseed, and fish oil (Fokkink et al, 2009;Górka et al 2011a;Hill et al, 2011;Kupczyński et al, 2017). The use of additives, especially those rich in PUFA, affects not only BW gain but also immune responses, antioxidant status, and overall metabolism (Calder et al, 2002;Hill et al, 2011;Karcher et al, 2014;Garcia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Iron was complexed with different proteins in the previous studies [3,[19][20][21] and used for application in different foods. In the present study, iron was complexed with WPC employing the process of centrifugation and UF.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was noted that the cooper easily binds to proteins and the excess of this metal may cause the effect of growth retardation, bone diseases, anaemia, teratogenesis or even Wilson's disease or idiopathic copper toxicosis [59]. Kupczyński et al (2017) [60] found that the high levels of microelements in the nutrition of ruminants may cause their bioaccumulation and toxic effects in the organism. It has also been reported that copper contributes significantly to the reduction of nutrient digestibility, lipid peroxidation, and causing oxidative stress in animals [60], which is greatly significant for animal welfare and for the quality of animal products [61].…”
Section: Monitoring Of Environmental Contamination With Toxic Metalsmentioning
confidence: 99%
“…Kupczyński et al (2017) [60] found that the high levels of microelements in the nutrition of ruminants may cause their bioaccumulation and toxic effects in the organism. It has also been reported that copper contributes significantly to the reduction of nutrient digestibility, lipid peroxidation, and causing oxidative stress in animals [60], which is greatly significant for animal welfare and for the quality of animal products [61]. It is also worth noting the fact that the copper deficiency in the organism may cause metabolic and immune disorders in humans and animals, which was confirmed by Harada et al (2020) [62].…”
Section: Monitoring Of Environmental Contamination With Toxic Metalsmentioning
confidence: 99%